Association of genetic variations in the mitochondrial DNA control region with presbycusis - Falah M (Dove Medical Press, 2017)
Masoumeh Falah,1 Mohammad Farhadi,1 Seyed Kamran Kamrava,1 Saeid Mahmoudian,1 Ahmad Daneshi,1 Maryam Balali,1 Alimohamad Asghari,2 Massoud Houshmand1,3 1ENT and Head & Neck Research Center and Department, Iran University of Medical Sciences, Tehran, Iran; 2Skull Base Research Center, Iran University of Medical Sciences, Tehran, Iran; 3Department of Medical Genetics, National Institute of Genetic Engineering and Biotechnology, Tehran, Iran Background: The prominent role of mitochondria in the generation of reactive oxygen species, cell death, and energy production contributes to the importance of this organelle in the intracellular mechanism underlying the progression of the common sensory disorder of the elderly, presbycusis. Reduced mitochondrial DNA (mtDNA) gene expression and coding region variation have frequently been reported as being associated with the development of presbycusis. The mtDNA control region regulates gene expression and replication of the genome of this organelle. To comprehensively understand of the role of mitochondria in the progression of presbycusis, we compared variations in the mtDNA control region between subjects with presbycusis and controls.Methods: A total of 58 presbycusis patients and 220 control subjects were enrolled in the study after examination by the otolaryngologist and audiology tests. Variations in the mtDNA control region were investigated by polymerase chain reaction and Sanger sequencing.Results: A total of 113 sequence variants were observed in mtDNA, and variants were detected in 100% of patients, with 84% located in hypervariable regions. The frequencies of the variants, 16,223 C>T, 16,311 T>C, 16,249 T>C, and 15,954 A>C, were significantly different between presbycusis and control subjects.Conclusion: The statistically significant difference in the frequencies of four nucleotide variants in the mtDNA control region of presbycusis patients and controls is in agreement with previous experimental evidence and supports the role of mitochondria in the intracellular mechanism underlying presbycusis development. Moreover, these variants have potential as diagnostic markers for individuals at a high risk of developing presbycusis. The data also suggest the possible presence of changes in the mtDNA control region in presbycusis, which could alter regulatory factor binding sites and influence mtDNA gene expression and copy number. Keywords: age-related hearing impairment, presbycusis, mtDNA control region, audiology